DOI: 10.35537/10915/82345
|View full text |Cite
|
Sign up to set email alerts
|

Composición y estructura de la comunidad de arañas en el sistema de cultivo de soja transgénica

Abstract: Las arañas son artrópodos depredadores generalistas que tienen como presa a la mayoría de los taxa de artrópodos, incluídas otras arañas. Pueden desempeñarse como efectivos enemigos naturales de insectos herbívoros en muchos agroecosistemas, debido a su presencia constante y relativamente alta abundancia durante todas las fases de desarrollo de los cultivos, y a su capacidad de dispersión y colonización. En la Argentina, a partir de 1996 ocurrió una gran expansión territorial del cultivo de soja consistente en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 151 publications
(262 reference statements)
0
0
0
Order By: Relevance
“…The soybean crop is inhabited by several herbivore arthropods some of which are pests, and also by natural enemies of herbivores, providing a biological control service of pest populations. Among these organisms, the predator Alpaida veniliae Keyserling 1895 (Araneae, Araneidae) is one of the most abundant species of the spider orb web weaving guild (Minervino 1996;Benamu 2010). Previous studies indicated that in addition to its high abundance, its biological and ecological attributes point out the importance of conservation this predator as a natural enemy of many soybean crop pests (Benamu ´et al 2011).…”
Section: Introductionmentioning
confidence: 99%
“…The soybean crop is inhabited by several herbivore arthropods some of which are pests, and also by natural enemies of herbivores, providing a biological control service of pest populations. Among these organisms, the predator Alpaida veniliae Keyserling 1895 (Araneae, Araneidae) is one of the most abundant species of the spider orb web weaving guild (Minervino 1996;Benamu 2010). Previous studies indicated that in addition to its high abundance, its biological and ecological attributes point out the importance of conservation this predator as a natural enemy of many soybean crop pests (Benamu ´et al 2011).…”
Section: Introductionmentioning
confidence: 99%